Common variants at 11p13 are associated with susceptibility to tuberculosis. - Thye, T; Owusu-Dabo, E; Vannberg, F; van Crevel, R; Curtis, J; Sahiratmadja, E; Balabanova, Y; Ehmen, C; Muntau, B; Ruge, G; Sievertsen, J; Gyapong, J; et al. (2012)
After imputation of data from the 1000 Genomes Project into a genome-wide dataset of Ghanaian individuals with tuberculosis and controls, we identified a resistance locus on chromosome 11p13 downstream of the WT1 gene (encoding Wilms tumor 1). The strongest signal was obtained at the rs2057178 SNP (P = 2.63 × 10(-9)). Replication in Gambian, Indonesian and Russian tuberculosis case-control study cohorts increased the significance level for the association with this SNP to P = 2.57 × 10(-11).